Implementasi Metode Simple Additive Weighting (SAW) untuk analisa kepuasan pasien terhadap layanan poli rawat jalan (Studi Kasus: Rumah Sakit Pertamina Bintang Amin) - agung deni (Jurnal Data Mining dan Sistem Informasi, 2022)
Hospital is a health service institution that provides complete individual health services that provide inpatient, outpatient, and emergency services. One of the hospitals in Lampung province has the motto "Excellent Service, Healthy Belongs to All", "We Care We Cure" which has the goal of becoming a referral hospital for hospitals in Lampung Province. With this goal, the hospital should provide excellent service to patients. Several ways are carried out by the hospital to measure how good the quality of existing services is, including by making a means of contact for criticism and suggestions as well as an sms center. However, the hospital has not implemented the measurement of patient satisfaction using any method so that the hospital has difficulty in measuring the quality of service and patient satisfaction. The author conducted research in hospitals to measure patient satisfaction. In calculating patient satisfaction using the SAW (Simple Additive Weighting) method by determining criteria such as registration services, doctors, nurses, pharmacies, cashiers, facilities and the weight value that has been determined by the number of respondents using Population and Sample calculations. Which is expected to help the hospital in assessing and knowing the satisfaction of outpatient poly patients.This study uses the Java programming language, MySQL database, uses a UML-oriented system design and tests the system program using black box testing, obtaining a value of 100% (Very Eligible). The results of this study are the highest ranking obtained on the criteria of doctors with a value of 0.297 and the lowest value is on registration with a value of 0.098.